2010
DOI: 10.1111/j.1744-7429.2010.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Weighing Defensive and Nutritive Roles of Ant Mutualists Across a Tropical Altitudinal Gradient

Abstract: The diversity of mutualistic interactions influences many ecological components of community structure, including biodiversity and ecosystem stability. However, mutualistic interactions are not well resolved because of a historical bias toward examining antagonistic interactions. Here we examine both antagonistic and facilitative interactions between tropical plants and arthropods by characterizing the biotic interactions between a common myrmecophytic shrub, Piper immutatum Trel. (Piperaceae), the ants hosted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…For example, studies in both tropical and temperate mountains have found increasing elevation to be associated with lower insect herbivore attack by parasitoids (Preszler andBoecklen 1996, Maunsell et al 2015), predatory arthropods (Koptur 1985, Rodríguez-Castañeda et al 2011, Rasmann et al 2014c, Sam et al 2015, Roslin et al 2017, and insectivorous birds (Sam et al 2015) (Fig. 1A).…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 98%
“…For example, studies in both tropical and temperate mountains have found increasing elevation to be associated with lower insect herbivore attack by parasitoids (Preszler andBoecklen 1996, Maunsell et al 2015), predatory arthropods (Koptur 1985, Rodríguez-Castañeda et al 2011, Rasmann et al 2014c, Sam et al 2015, Roslin et al 2017, and insectivorous birds (Sam et al 2015) (Fig. 1A).…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 98%
“…; Rodriguez‐Castaneda et al . ). For instance, ants are frequently involved in plant indirect defences (Beattie ), as they are the dominant insect predators in many different ecosystems (Holldobler & Wilson ).…”
Section: Introductionmentioning
confidence: 97%
“…In parallel, the need to attract a predator partner should decrease with increasing elevation (Rodriguez‐Castaneda et al . ). On the other hand, as high‐elevation plants might suffer from a reduction in metabolic activity and growth due to poorer soil quality and colder temperatures, we might predict an increase in low‐cost inducible defences at high elevation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…viridiflava (Dognin) (Fig. 4B–H; Rodríguez-Castañeda 2009, Dyer et al 2013: www.caterpillars.org ). Seven of these species were recognizable from adult characters as distinct species, whereas additional cryptic species were recognized from a combination of molecular data and larval characteristics (Wilson et al 2012).…”
Section: Resultsmentioning
confidence: 99%